A Comparative Study of Authentic Listening Materials for Non-English Major College Students - Puspita, Puspita; Suswanto, Suswanto (Institut Agama Islam Negeri Parepare, 2023)
Broadly listening, non-English major students encounter bigger difficulties in learning English because they have a shorter time indirectly contacting or using the language. An important factor that should be taken into consideration is the use of appropriate authentic listening materials in the classroom. The objectives of the research were aimed to investigate whether there is a significant difference in students' listening comprehension using audio media versus video media and to determine which of these media is effective in enhancing students' listening comprehension. This research used a quantitative method with a quasi-experimental design. It was conducted in two classes of first-grade students of State Polytechnic of Agriculture Samarinda as non-English major college students. The classes comprised class PPIIA as the experimental group using audio and PPIIB as the control group using video. The researchers used pre-test and post-test designs to collect the data. The result of the data revealed that there was a significant difference between students' listening comprehension using audio media versus video media. Teaching listening using video is more effective in enhancing students' listening comprehension because video can provide visually attractive and enjoyable listening practice for students in the classroom.